Situation Report: Czechoslovakia, 2 July 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hard-Liners Reiterate Their Position Vaclav Havel's "Anatomy of a Certain Wariness" Considering the "Right to Work" Czechoslovakian Still Reluctant to Take a Second Bit of the Reformist Apple